Study of a novel adaptive bit loading and power control scheme for OFDM systems - Song, Zhefeng. (2008)
In this thesis, we begin by investigating the fading characteristics of OFDM subcarriers and discover that some OFDM channels exhibit non-uniform subcar-rier fading distributions. For such channels, we propose a novel adaptive modula-tion scheme to achieve better spectral efficiency, transmission power savings and equalized subcarrier bit error rates (BERs) for OFDM systems. As the proposed scheme effectively performs adaptive bit loading and power control on the OFDM subcarriers based on their fading statistics instead of instantaneous fading gains, we call it a "statistical OFDM adaptation" scheme.